Jumpstart CMM/CMMI software process improvement : - Land, Susan K. (Wiley, 2005)
This book provides invaluable guidance on moving an organization from the chaotic environment of free-form software development towards a more controlled and documented process. It discusses how IEEE standards may be used to facilitate the development of internal plans and procedures in support of repeatable software engineering processes, or in achiving CMM/CMMI-SW Level 2.